Microsatellites markers associated with resistance to flower bud thrips in a cowpea F2 population derived from genotypes TVU-123 and WC36 - Agbahoungba, Symphorien; Karungi, Jeninah; Sadik, Kassim; Gibson, Paul; Edema, Richard; Assogbadjo, Achille E.; Rubaihayo, Patrick R. (African Journal of Biotechnology, 2018)
Breeding for resistance to flower bud thrips (Megalurothrips sjostedti) in cowpea has been hindered by the quantitative nature of resistance. To identify simple sequence repeat (SSR) markers associated with resistance to flower bud thrips that could be used for marker-assisted breeding, a F2 population was generated from a cross between genotypes TVU-123 (resistant) and WC36 (susceptible). The population was evaluated for thrips damage scores, thrips counts, and pods number per plant under artificial infestation. Sixty-six microsatellites markers were screened between the two parental lines and seven polymorphic markers were used for genotype 100 F2 plants. Single marker analysis was used to evaluate an association between the markers and traits. Transgressive segregation among the F2 plants for resistance to flower thrips was observed. A significant negative relationship was observed between thrips damage scores and pods number per plant. Markers CP37/38 and CP215/216 were significantly associated with thrips damage scores and thrips counts, respectively. The two markers explained 7 and 11.2% of the total variation in thrips damage scores and thrips counts with positive and negative effects, respectively. Mainly additive gene effects were observed. A more detailed study using more markers on these loci should provide better understanding of this complex trait.
Keywords: Cowpea; Single marker analysis; Polymorphism; Simple sequence repeat (SSR) markers